Effectiveness and Physical Quality Test of Ashitaba Leaf Extract Exfoliating Toner against Staphylococcus epidermidis and Propionibacterium acnes - Luluk Aniqoh Meliana Putri; Devita Riafinola Andaririt (Griya Eka Sejahtera, 2026)
Background: Acne (acne vulgaris) is a chronic inflammatory skin disease with a complex pathogenesis, involving the sebaceous glands and excessive colonization of acne-causing bacteria. In the modern era, the trend of using natural cosmetics is gaining momentum, not only in Indonesia but also globally. An example of a plant with great potential is Ashitaba. Ashitaba leaves have antibacterial. This study aimed to observe the physical quality test and antibacterial test of ashitaba leaf extract toner against Staphylococcus epidermidis and Propionibacterium acnes bacteria.Methods: The design in this study is an experimental method, physical quality tests include, Organoleptic tests are carried out visually, the components evaluated are the smell, shape, color and texture of the preparation, pH test and viscosity test. analysis of data from the physical quality test of the Ashitaba leaf extract facial toner, the physical characteristics of the preparation, including organoleptic, homogeneity, viscosity, and pH, of all three formulas met the parameters.Results: The toner tested against Staphylococcus epidermidis and Propionibacterium acnes bacteria had the largest inhibition zone, namely with an extract concentration of 20%.Conclusion: The toner tested against Staphylococcus epidermidis bacteria with a 20% extract had the largest inhibition zone of 27.6 mm, while Propionibacterium acnes bacteria with a 20% extract had the largest inhibition zone of 27.9 mm